Linkage of Money Growth on Inflation and Economic Growth - Evidence from Indonesia - Sipahutar, Mangasa Augustinus (Jurnal Economia, 2024)
AbstractThis study is about money growth, and its linkage on inflation and economic growth. It was found that money growth in the previous period affected by 0.1539 on changing of economic growth, inflation affected by -0.2637 on economic growth, and money growth affected changing of inflation by 1.0468. Money growth is a source of economic growth but it will then induce economic shocks stemming from inflation, then money growth must refer to normal growth. It was found that normal money growth is 16.7631%. Because deviation of money growth in a certain period from its normal growth will affect inflation and economic growth, money growth must be controlled by a small deviation from its normal growth. This method on determining normal money growth can be used as reference to Bank Indonesia in determining economic growth and inflation, and to commercial banks in determining interest rates. Keywords:Economic Growth, Inflation, Money Growth, Normal Growth of Money